Analysis of the Influence of Customer Experience and Lifestyle on Unesa Students' Film Watching Decisions at the XXI Cinema Building in Surabaya - Erta, Erta; Dewi, Hapsari Shinta Citra Puspita (International Journal of Emerging Research and Review, 2024)
Objectives: The Indonesian film world has experienced a decline in recent years due to the pandemic, apart from that technological innovation has given rise to practical ways of showing films that can be accessed anytime and anywhere. Although technological updates have not reduced the interest of offline viewers at XXI Cinema. The aim of this research is to influence consumers' lifestyles or experiences in watching cinema at XXI to increase students' interest in watching. Method:  The method used in this research is qualitative research to see the influence of customer experience and lifestyle on the decision to watch the XXI cinema among Universitas Negeri Surabaya (Unesa) students. Results: There is an influence from variables or lifestyle aspects that Surabaya State University students have on the decision to watch a film at the XXI Cinema Building. The second variable has no effect on purchasing decisions. In fact, lifestyle variables influence the decision to purchase cinema tickets at Building XXI. However, when put together, it has no effect because there is influence from other variables. There are several items in the customer experience that have no effect on purchasing decisions and the influence of lifestyle variables is very large. From the attached data, the decision to purchase cinema tickets at XXI will be purchased taking into account promotions, events, lifestyle and cinema facilities. Novelty: The novelty of this research focuses on the research sample, namely Unesa students who belong to generation Z and also students who have the ability to buy cinema tickets for the upper middle class XXI.